Respuesta :
To solve for c in terms of a and b, we can rearrange the given equation:
bc + ac = ab
First, we can isolate the term with c by subtracting ab from both sides:
bc + ac - ab = ab - ab
This simplifies to:
bc + ac - ab = 0
Now, we can factor out c:
c(b + a) = 0
To find the value of c in terms of a and b, we can divide both sides by (b + a):
c = 0 / (b + a)
Since any number divided by zero is zero, we get:
c = 0
bc + ac = ab
First, we can isolate the term with c by subtracting ab from both sides:
bc + ac - ab = ab - ab
This simplifies to:
bc + ac - ab = 0
Now, we can factor out c:
c(b + a) = 0
To find the value of c in terms of a and b, we can divide both sides by (b + a):
c = 0 / (b + a)
Since any number divided by zero is zero, we get:
c = 0
Answer:
[tex] \frak{c = \dfrac{ab}{(b + a)} }[/tex]
Step-by-step explanation:
Given Equation :
- bc + ac = ab
We have to find :
- Value of c in terms of a and b
Solution :
[tex] \sf{ \dashrightarrow \: \: \: \: bc + ac = ab}[/tex]
Taking out c as common factor from bc and ac :
[tex] \sf{ \dashrightarrow \: \: \: \: c(b + a) = ab}[/tex]
Dividing both sides with ( b + a ) :
[tex]\sf{ \dashrightarrow \: \: \: \: \dfrac{c \cancel{( b + a) }}{ \cancel{(b + a})}= \dfrac{ab}{(b + a)}}[/tex]
We get :
[tex]\sf{ \dashrightarrow \: \: \: \: \underline{ \boxed{ \bold{ c= \dfrac{ab}{(b + a)}}}}} \: \: \: \bigstar[/tex]
>>> Therefore , value if c in terms of a and b is "ab/(b+a)".
VERIFICATION :
[tex] \sf{ \longmapsto \: \: \:bc + ac = ab }[/tex]
[tex] \sf{ \longmapsto \: \: \: c(a + b) = ab}[/tex]
Plugging in value of c i.e. ab/(a+b) :
[tex] \sf{ \longmapsto \: \: \: \left(\dfrac{ab}{ \cancel{(a + b)}} \right) \cancel{(a + b)} = ab}[/tex]
Simplifying :
[tex] \sf{ \longmapsto \: \: \: ab = ab}[/tex]
[tex] \sf{ \longmapsto \: \: \: LHS = RHS}[/tex]
[tex]\sf{ \longmapsto \: \: \: Hence, Verified.}[/tex]